SHM_1227470_HST_3D Hollow-Edged Stone Axe - National Historical Museums (National Historical Museums, 2026)
Structured Light 3D model of a hollow edged stone axe from the Swedish Neolithic, collected in the field from Marka in Hallsberg parish, Närke, Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=402

Link to Sök I Samlingarna

https://samlingar.shm.se/object/E055AC71-A943-43C3-8121-BF4E21FE1453
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Structured Light Scanning; Dynamic Collections; 3D Model; Museum Object; Swedish Neolithic; Marka; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi